Abdominal cryptococcosis in dogs and cats: 38 cases (2000‐2018). (26th October 2020) - Johnston, L.; Mackay, B.; King, T.; Krockenberger, M. B.; Malik, R.; Tebb, A.
Abstract : Introduction: To report the clinical presentation, laboratory and imaging findings, treatment and outcome of abdominal cryptococcosis in dogs and cats in Australia. Materials and Methods: Canine and feline cases from Australia were retrospectively identified (2000 to 2018) via laboratory and referral centre searches for abdominal cryptococcosis diagnosed by cytology (needle aspirates) or histopathology (biopsy or necropsy) of abdominal organs/tissues. Signalment, presenting complaints, clinical signs, laboratory findings, medical imaging, latex cryptococcal antigen agglutination test (LCAT) titres, treatment and outcome data was collected. Results: Thirty‐eight cases were included (35 dogs, three cats) in the study. Median age of presentation was 2 years for dogs and 6 years for cats. Common presenting complaints included vomiting (23/38), lethargy (19/38) and inappetence/anorexia (15/38). Abdominal ultrasound (25/38 cases) revealed mesenteric and intestinal lesions in most of the cases. On surgical exploration, seven cases had an intestinal lesion associated with an intussusception. Nineteen cases had a pre‐treatment LCAT performed, with a median initial titre of 1:2048 (range 1:2 to 65, 536). Twenty‐four cases (23 dogs, one cat) received treatment, either medical, surgical or both. Median survival time for cases with combined medical and surgical treatment, surgical treatment alone or medical treatment alone was 730, 140 and 561 days, respectively. Eleven remain alive at the time of follow up. Clinical Significance: Abdominal cryptococcosis although rare should be a considered as a diagnostic possibility in an especially young dog presenting with gastro‐intestinal signs. Older dogs can also present with this condition and should not be euthanised based on imaging alone due to the likenesses with neoplasia. With appropriate treatment and monitoring many dogs may have a prolonged survival period and some may be cured.